Edukasi Pencegahan Asthenopia (Kelelahan Mata) Selama Pembelajaran Daring Pada Mahasiswa - Yunita Liana Yuni; Meta Nurbaiti; Mareta Akhriansyah (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The use of mobile technology influences educational institutions, including the achievement of distance learning goals. Various media are used to support the implementation of online learning. One of the gadget media used in online learning is the smartphone. The use of digital devices (smartphones) for a long time is one of the consequences of eye fatigue (asthenopia). The purpose is to increase students' knowledge about preventing asthenopia (eye fatigue) during online learning. The form of community service activities through education are lectures and discussions. The target of the activity is the students of Stik Bina Husada Palembang. The implementation time is June 22, 2022. The media used is google meet. Evaluation methods include; pretest and posttest on students' knowledge about preventing asthenopia during online learning. The instrument for evaluation is a google form distributed before and after educational activities. Data of community service activities were analyzed using descriptive analysis techniques. The educational activities that have been carried out have a positive impact on students' knowledge about preventing asthenopia during online learning